Critical Indicators on Macro Economics adoption in GDP: A systematic review - Abdullahi Sule, Sani (The Es Economics and Entrepreneurship, 2024)
The study's goal is to investigate how important macroeconomic factors affect certain African nations. These metrics are crucial for the economies' effective development and can be utilized to address the many economic issues that the chosen countries are currently dealing with. 91 publications published between 2004 and 2022 were examined using the Scopus database. With an emphasis on five major factors: Growth Domestic Product (GDP), Interest Rate, Exchange Rate, Inflation, and Foreign Direct Investment this study evaluated and analyzed the literary elements and themes explored in order to give guidance for future research. The findings revealed that Interest rates, inflation, exchange rates, and foreign direct investment (FDI) are some of the macroeconomic variables that can affect the selected African economies. Foreign direct investment has been identified as the most important factor in improving industrial prosperity and living standards in developing economies such as Nigeria, South Africa, Egypt, Algeria, and Morocco after stabilizing interest rates, inflation and currency exchange rates. The study's findings are supported by material that has been published in previous years. Given that a number of recent economic issues have had an impact on the expansion of the economy, it is necessary to evaluate the ideas using panel data from the past 20 years in order to ascertain whether they are still valid. The report highlights the key macroeconomic factors that may have an impact on five different African economies. The study combines a number of economic metrics that have previously been studied separately to assess the trend in the economies it has chosen. To the best of my knowledge, this study is one of the few that evaluates both the individual countries used and the indicators in general.